2021
DOI: 10.17533/udea.iee.v39n2e05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Interventions to Reduce Readmissions due to Heart Failure Decompensation in Adults: a Systematic Review and Meta-analysis

Abstract: Objective. To estimate the combined effect of educational interventions (EI) on decreased readmissions and time of hospital stay in adults with heart failure, compared with usual care. Methods. Systematic review (SR) and meta-analysis (MA) of randomized controlled trials that followed the recommendations of the PRISMA statement. The protocol was registered on PROSPERO (CRD42019139321). Searches were made from inception until July 2019 in the databases of PubMed/Medline, Embase, Cochrane CENTRAL, Lilacs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 58 publications
0
9
0
2
Order By: Relevance
“…Of the eight systematic reviews [20][21][22][23][24][25][26][27] , six included a meta-analysis of the impact on HF readmissions, [20][21][22][23][24][25] six examined all-cause readmissions, 20,[22][23][24][26][27] five investigated all-cause mortality outcomes, 20,23,24,26,27 and two reviews examined HF mortality. 20,24 The full details of each systematic 1332 review are provided in Supporting Information, Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the eight systematic reviews [20][21][22][23][24][25][26][27] , six included a meta-analysis of the impact on HF readmissions, [20][21][22][23][24][25] six examined all-cause readmissions, 20,[22][23][24][26][27] five investigated all-cause mortality outcomes, 20,23,24,26,27 and two reviews examined HF mortality. 20,24 The full details of each systematic 1332 review are provided in Supporting Information, Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…This narrative meta-synthesis is the first review to analyse the outcomes of DSMS interventions based on intervention intensity. The findings suggest that DSMS programmes can significantly reduce acute care readmissions [20][21][22][23][24]26,27 and improve survival. 20,23,24,26,27 Although low-intensity DSMS programmes have some influence on HF readmissions, we found little evidence of their impact on mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review and meta-analysis of 47 studies reported the success of home-visiting programs and multidisciplinary HF clinics in reducing all-cause readmission and mortality, and of structured telephone support in reducing HF-specific readmission and mortality [ 60 ]. Similarly, results from another systematic review and meta-analysis highlight the importance of educational interventions on HF in reducing readmissions and length of hospital stay in adults with HF [ 61 ]. Many of these educational interventions, however, were implemented by experienced cardiovascular nurses.…”
Section: Main Textmentioning
confidence: 99%